2019
DOI: 10.1136/neurintsurg-2019-015145
|View full text |Cite
|
Sign up to set email alerts
|

Transradial access for neurointerventions: management of access challenges and complications

Abstract: BackgroundNumerous large randomized trials have shown a significant morbidity and mortality benefit with the transradial approach (TRA) over the transfemoral approach (TFA) for endovascular procedures. However, this technique is routinely avoided or aborted due to unfamiliarity with the technique and the associated anatomical difficulties that may be faced in this approach. The objective of this review is to identify both the common and uncommon challenges that may be encountered during a transradial approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 43 publications
0
64
3
1
Order By: Relevance
“…The radial artery approach has become an increasingly popular alternative for arterial access in endovascular interventions 1. First described by Campeau2 nearly three decades ago, the use of a percutaneous radial artery approach for angiography has seen a significant increase in the field of interventional cardiology owing to comparative data demonstrating superiority in clinical outcome, patient satisfaction, and cost reduction compared with the standard femoral artery access 2–11.…”
Section: Introductionmentioning
confidence: 99%
“…The radial artery approach has become an increasingly popular alternative for arterial access in endovascular interventions 1. First described by Campeau2 nearly three decades ago, the use of a percutaneous radial artery approach for angiography has seen a significant increase in the field of interventional cardiology owing to comparative data demonstrating superiority in clinical outcome, patient satisfaction, and cost reduction compared with the standard femoral artery access 2–11.…”
Section: Introductionmentioning
confidence: 99%
“…Two cases of asymptomatic radial occlusion were recorded at the beginning of our training experience, maybe due to bend error in decompression timing. In previous studies, compression time and pressure have been shown to contribute to radial artery occlusion (Cubero et al 2009 ); moreover, radial complication events (puncture failure, artery spasm and occlusion) would be less frequent as the interventionist gains experience (Liu et al 2019 ; Brunet et al 2020 ). In fact, Snelling et al ( Snelling et al 2018b ) demonstrated that the learning curve of the radial access rapidly improve between case 5 and case 15 in a neurointerventional scenario.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, while neurointerventional procedures can be safely and successfully performed via 6 French and 7 French systems, their size may also increase the risk of RAO, precluding future TRA access. Accordingly, it is imperative to employ strategies to minimize the risk of RAO such as using the minimal size sheath or catheter that is necessary to accomplish the procedure, administering heparin and antispasmodics, and careful use of compression devices to close the arteriotomy with patent hemostasis 12 13 29…”
Section: Discussionmentioning
confidence: 99%
“…During the study period, operators included three neurointerventionalists (DRY, RMS, ECP) and six neurointerventional fellows (BS, SS, JC, PK, MCB, SC). We have previously described the set-up and technical details of our transradial procedures 4 12 15–19. Diagnostic cerebral angiography was performed with a 100 cm hydrophilic coated 5 French Simmons 1, Simmons 2, or Simmons 3 catheter through a 5 French radial sheath.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation